An Investigation of Algerian Dates (Phoenix dactylifera L.); Antioxidant, Anti-inflammatory Properties and Phenolic Compositons H - Bendiab, Hadjer Chenini; Djebli, Noureddine; Kara, Yakub; Uçar, Meltem; Kolayli, Sevgi (Emirates Journal of Food and Agriculture, 2021)
Date fruit (Phoenix dactylifera L.) is not only known for its nutritional properties but also its therapeutic virtues. The objective was to investigate the phenolic compounds and evaluate the antioxidant and anti-inflammatory activities of pulp, seed, and whole fruit of Algerian dates. The total phenolic and flavonoid contents of ethanolic pulp (EP), seed (ES), and whole fruit (EF) extracts were measured using colorimetric methods. Phenolic acids and flavonoid profiles were determined by RP-HPLC-UV. The examination of the antioxidant potential was established by Free radical scavenging DPPH and FRAP assays. Anti-inflammatory activity of aqueous pulp (AP), seed (AS), and whole fruit (AF) of dates at 100, 200, and 300 mg/kg BW of each extract were carried out according to the experimental model of carrageenan-induced acute paw edema in mice, using diclofenac (50 mg/kg) as a reference product. Measurement of the percentage of inhibition of paw edema in mice as well as the histological study of the paw tissue, allowed us to assess the anti-inflammatory effect of the extracts investigated. Ethanolic pulp, seed, and whole fruit of date extracts contained total phenolic and flavonoids compounds at different concentrations as well as a diverse phenolic profile. The strongest antioxidant capacity was determined in ethanolic date seed extract. Concerning anti-inflammatory activity, the administration of aqueous pulp (100 and 200 mg/kg), seed (100mg/kg), and fruit (100, 200, and 300 mg/kg) of date extract induced a higher anti-inflammatory response from the fourth hour after carrageenan injection compared to the standard group treated with diclofenac. It is concluded that pulp, seed, and whole fruit of Algerian date possess antioxidant activity with phenolic and flavonoid contents and anti-inflammatory activity and dates with pulp and seed parts could be used as a natural bioactive substance for supporting anti-inflammatory therapies.